HELLP syndrome: critical insights from a post-cesarean involving rapid hemoglobin drop - Medani, Isameldin Elamin (International Journal of Research in Medical Sciences, 2025)
HELLP (Hemolysis, elevated liver enzymes and low platelets) syndrome is a severe form of preeclampsia characterized by hemolysis, elevated liver enzymes, and low platelet count. It can lead to significant maternal morbidity and mortality if not promptly diagnosed and treated. A 32-year-old female, G2P1A0L1, at 38 weeks gestation, presented with labor-like pain, vaginal leaking, lower limb edema, and high blood pressure. She was diagnosed with severe preeclampsia and underwent an emergency cesarean section. Post-operatively, her hemoglobin dropped from 13 g/dL to 6 g/dL despite blood transfusions. Imaging and tests excluded internal bleeding but revealed mild pleural effusion and pelvic fluid collection. Liver function tests revealed thrombocytopenia and increased liver enzymes, which led to a diagnosis of HELLP syndrome. Supportive treatment with fresh frozen plasma, platelets, and packed RBCs was administered. Early identification and treatment of HELLP syndrome is necessary in patients with severe preeclampsia and notable postoperative hemoglobin reduction. Supportive treatment led to clinical improvement and normalization of this patient's hemoglobin levels, blood pressure, liver enzymes, and platelet counts.